No smoke, no need to destroy 'ketum' tree - Abd Razak, Dzulkifli (2005)
RECENTLY there was this call, again, to look for a now way of dealing with the problem of drug abuse in the country. It looks like we are caught at a crossroad as a result of our own doing. Fortunately, the Ministry of Internal Security (Malay Mail, April 14) "is willing to consider the proposal to provide drugs to addicts as part of its effort to fight drug addiction in the country". The ministry's Parliamentary Secretary was quoted as saying that "the idea of supplying drugs could be traced back in history, when opium shops were licensed to supply the drug to addicts". This is in tandem with an observation made by an MP "that the mandatory death sentence on drug traffickers has not been effective in curbing the problem". Thus it follows: It is better to give them (addicts) drugs and let them live their lives the way they want?